Production and Efficiency of Pond Fish Farming Business Milkfish - Sudarmo, Hadi; Fyka, Samsul Alam (HABITAT, 2017)
Various different factors, either direct or indirect one, contribute to decreasing production of milkfish in milkfish farms located in North Konawe. Production of milkfish in the area is relatively low and it is predicted that the milkfarmersâ inability to either allocate inputs or maximize the use of the inputs becomes the cause. Therefore, the objectives of the study were to analyze the line of production factors and production efficiency of milkfish farm in South Konawe. Path analysis was the method to analyze the direct and indirect factors affecting the production of the milkfish farm while marginal product value was the one used to analyze the price efficiency and optimal input. The findings of the study indicated that: the factors that directly affected production were the number of seed and employees as well as the amount of fertilizer while the factors indirectly affecting production were the number of seeds and employees as well as the amount of fertilizer. The milkfish farms in North Konawe would become efficient when there were 7,606 milkfish seeds, 41 employees and 427 kilograms of fertilizer.